Growth Hormone Cotreatment for Low-Prognosis Patients According to the POSEIDON Criteria - Liu, Xueying; Xu, Jingxiao; Bi, Lixin; Liu, Peihao; Jiao, Xue (Frontiers in Endocrinology, 2021)
Background: Poor ovarian response (POR) remains one of the most challenging conditions in assisted reproduction technology. Previous studies seemed to indicate that growth hormone (GH) was a potential solution for the dilemma of POR; however, the role GH played on the low prognosis patients diagnosed and stratified by the POSEIDON criteria remains indistinct. Methods: This retrospective study was performed among women with POR according to the POSEIDON criteria who failed a previous in vitro fertilization (IVF) /intracytoplasmic sperm injection (ICSI) cycle and the subsequent cycle was under GH cotreatment and conducted within 12 months. These participants were stratified into four groups according to the POSEIDON criteria. The comparison was implemented between the failed cycle and the cycle treated with GH. Generalized estimating equations (GEE) multivariate regression was applied for data analysis. Results: A total of 428 low-prognosis women were included in this study. GH supplementation improved the live birth rates (47.66%, 28.33%, 45.45% and 24.07%; in group 1, 2, 3 and 4 respectively) and the clinical pregnancy rates (OR 19.16, 95% CI 7.87-46.63, P < 0.001; OR 7.44, 95% CI 1.65-33.55, P = 0.009; OR 10.19, 95% CI 2.39-43.52, P = 0.002; OR 27.63, 95% CI 4.46-171.11, P < 0.001; in group 1, 2, 3 and 4 respectively) in all four POSEIDON groups. The number of oocytes retrieved was significantly elevated in the sub-groups with normal ovarian reserve (IRR 1.47, 95% CI 1.36-1.59, P < 0.001; IRR 1.31, 95% CI 1.15-1.49, P < 0.001; in group 1 and 2 respectively). The number of day-3 good-quality embryos was significantly elevated in the sub-groups with either normal ovarian reserve or aged young (IRR 2.13, 95% CI 1.78-2.56, P < 0.001; IRR 1.54, 95% CI 1.26-1.89, P < 0.001; IRR 1.47, 95% CI 1.10-1.98, P = 0.010; in group 1, 2 and 3 respectively). Conclusion: Growth hormone cotreatment could ameliorate the pregnancy outcome for women with POR under the POSEIDON criteria who failed a previous IVF/ICSI cycle. The application of growth hormone for low prognosis women who experienced a failed cycle might be considered and further studied.